The Attitude of Fisher Folks Towards Agricultural Extension Services in Niger Delta, Nigeria - Tawari, C.C.; Davies, O.A. (International Journal of Pharma and Bio Sciences, 2010)
The fisher folks of Niger Delta have little knowledge about the importance of agricultural extension services thus they are not fully utilizing their services. The agricultural extension agents play important and critical roles in increasing farmer’s knowledge of scientific agriculture, improving their productive skills and influencing them to accept desirable changes in the farm and home management. The attitude of fisher folks towards agricultural extension services in enhancing and promoting fisheries development and management in their areas of operation within the Niger Delta was evaluated. Structured questionnaire was administered to one thousand fishers in four different states of the Niger Delta. The data collected were analyzed using mean, percentage, Likert-format scale and ranking. Data showed that 40% of respondents strongly agreed and 30% agreed that the extension officers enjoyed the confidence of the people, while 20% disagreed and 10% strongly disagreed. Training and Visit System (T&V) (2.03), as a strategy for fisheries development and management was regarded by the fishers as the most effective system. This was followed closely by Small Plot Adoption Technique (SPAT) (1.95), demonstration (1.90), contact group (1.76), integrated rural development (1.45) and literature (1.20). The results further showed that about 50% of respondents disagreed while 40.5% agreed that the extension officers had been able to encourage the citizenry to take to fishing and fish farming. Most of the fishers (50.3%) agreed and 43.2% disagreed that the agencies have succeeded in making fishing practice profitable.The results of the study showed that fishers in the study area were aware of the services of extension officers but the fishers rating of their effectiveness was low.